The risks of perinatal HIV/HCV co-infection and the evolution of treatment tactics of the disease in children (clinical case) - A. A. Khamatova; T. A. Chebotareva; J. F. Vlatskaya (Детские инфекции (Москва))
HIV infection and HCV infection are still serious and widespread infections that lead to high morbidity and mortality of the population worldwide.The aim is to assess the risks of perinatal transmission of HIV/HCV co-infection and the choice of modern treatment tactics in children.Аnalyzed data in foreign and domestic literature. A clinical case of perinatal transmission of HIV/HCV co-infection is described.Results. Тhe features of perinatal transmission of infection depending on its variants (mono-HIV infection, hepatitis C and co-infection with HIV/HCV) and risk factors are shown. A clinical example demonstrates the implementation of perinatal transmission of HIV/HCV co-infection in the presence of major risk factors. The improvement of therapeutic tactics in a child with co-infection is shown.Conclusion: in the described clinical case, numerous risk factors for perinatal transmission of HIV/HCV co-infection are demonstrated, the presence of which led to the realization of co-infection in a child. The effectiveness of modern tactics for the treatment of HIV infection and chronic viral hepatitis C has been demonstrated.